2014
DOI: 10.4236/as.2014.512126
|View full text |Cite
|
Sign up to set email alerts
|

Response of African Catfish, <i>Clarias gariepinus</i> (Burchell 1822), Fingerlings Fed Diets Containing Differently Timed Wet-Heat-Treated Sesame (<i>Sesamum indicum</i>) Seedmeal

Abstract: The response of catfish fed differently timed wet-heat-treated sesame seedmeal was evaluated in the diet of Clarias gariepinus using growth performance, nutrient utilisation and apparent digestibility coefficient as indices. Three batches of sesame seed, which were cooked for 10, 20 and 30 minutes, dried, milled, and mechanically defatted using locally made screw press. Each of these differently processed seedmeals was included in the diet of African catfish at varying replacement levels, 15, 30 and 45% with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…In parallel, the apparent net protein retention (ANPR) were higher in 15SSM and 20SSM groups than the C and 10SSM groups. While the values obtained in this study showed similarity with the study of Emadi et al (2014) who determined the crude protein rate of fish fillet as 24.2% in the group fed by diet containing 20% sesame seed meal, they were higher than the studies of Mukhopadhyay and Kay (1999), Jimoh et al (2014) and Jimoh and Aroyehun (2011) who detected it as between 8.01 and 8.90%, 17.42 and 17.70%, 13.7 and 13.9%, 16.00 and 16.86%, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In parallel, the apparent net protein retention (ANPR) were higher in 15SSM and 20SSM groups than the C and 10SSM groups. While the values obtained in this study showed similarity with the study of Emadi et al (2014) who determined the crude protein rate of fish fillet as 24.2% in the group fed by diet containing 20% sesame seed meal, they were higher than the studies of Mukhopadhyay and Kay (1999), Jimoh et al (2014) and Jimoh and Aroyehun (2011) who detected it as between 8.01 and 8.90%, 17.42 and 17.70%, 13.7 and 13.9%, 16.00 and 16.86%, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…While the highest lipid ratio was obtained in 10SSM group, there was a decrease in the crude lipid of fish fillet in 15SSM and 20SSM groups. While the values obtained from the study showed similarity with the study of Mukhopadhyay and Kay (1999) who determined the crude lipid rates of fish fillet as 4.29 to 5.24%, they were lower than the studies of Emadi et al (2014), Jimoh et al (2014) and Mohanta et al (2007) who detected the crude lipid rates of fish fillet as 7.4%, between 5.73 and 5.87% and between 6.5 and 6.7%, respectively. In the above-mentioned studies, a visible reduction occurred in the crude lipid of fish fillet with increasing amount of sesame seed meal in the diet but the differences were not statistically significant (p˃0.05).…”
Section: Discussionsupporting
confidence: 77%
“…The values of amino acid in the diets containing CM were equal to or slightly higher than control (0%), which can be considered negligible. All EAA tested in this study were compared with the EAA requirement for catfish as reported by Jimoh et al (2014) and Fagbenro and Nwanna (1999). Methionine, lysine and tryptophan were comparatively less than the required amount of amino acid for African catfish.…”
Section: Resultsmentioning
confidence: 93%
“…Notes: EAA requirement (g 100g −1 crude protein) according to Jimoh et al (2014): arginine 3.6, histidine 1.2, isoleucine 2.0, leucine 3.5, lysine 4.8, methionine 2.4, phenylalanine 4.0, threonine 2.8, valine 2.4 while tryptophan 1.1 according to Fagbenro and Nwanna (1999). Values are means of duplicates samples.…”
Section: Fishmealmentioning
confidence: 99%
“…Interestingly, Da, Lundh, and Lindberg (2012) revealed that the use of soybean meal and rice co-products as the single protein source did not compromise growth performances in striped catfish (Pangasianodon hypophthalmus). In African catfish Clarias gariepinus, nutritional in vivo experiments focusing on FM replacement by plant products have revealed heterogeneous growth responses which could be attributable to substitution degree and plant protein source (Imorou Toko, Fiogbe, & Kestemont, 2008;Jimoh & Aroyehun, 2011;Jimoh, Fagbenro, & Adeparusi, 2014;Nyina-Wamwiza, Wathelet, & Kestemont, 2007;Nyina-Wamwiza et al, 2010). Globally, it has been shown that partial or full substitution of FM by vegetable sources such as lupine meal, soybean meal, bean, cottonseed cake, sunflower oilcake, sesame seed meal and soybean cake (SC) does not affect reproduction and growth performances in African catfish.…”
Section: Introductionmentioning
confidence: 99%